2013
DOI: 10.1016/j.pain.2013.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortex and mediodorsal thalamus reduced connectivity is associated with spatial working memory impairment in rats with inflammatory pain

Abstract: The medial prefrontal cortex (mPFC) and the mediodorsal thalamus (MD) form interconnected neural circuits that are important for spatial cognition and memory, but it is not known whether the functional connectivity between these areas is affected by the onset of an animal model of inflammatory pain. To address this issue, we implanted 2 multichannel arrays of electrodes in the mPFC and MD of adult rats and recorded local field potential activity during a food-reinforced spatial working memory task. Recordings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 82 publications
5
47
0
Order By: Relevance
“…Its projections to the PAG, thalamus and amygdala have been studied in the context of chronic pain (Bushnell et al, 2013; Cardoso-Cruz et al, 2013; Ji and Neugebauer, 2014). There is recent evidence that connections between the PFC and the NAc—an important projection within the reward circuitry (Koob and Volkow, 2010)—are distinctly altered by chronic pain (Baliki et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Its projections to the PAG, thalamus and amygdala have been studied in the context of chronic pain (Bushnell et al, 2013; Cardoso-Cruz et al, 2013; Ji and Neugebauer, 2014). There is recent evidence that connections between the PFC and the NAc—an important projection within the reward circuitry (Koob and Volkow, 2010)—are distinctly altered by chronic pain (Baliki et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Gamma oscillation was shown to participate in the abnormal working memory of chronic pain (Cardoso-Cruz et al, 2013); however, whether oscillatory gamma oscillations play a role in the pain perception in chronic pain is unknown and of great interest. Unlike acute and tonic pain, chronic pain is a pathological, ongoing, and long-lasting condition (Merskey and Bogduk, 1994), featured by its persistence and maintenance of pain.…”
Section: Introductionmentioning
confidence: 99%
“…Some pathological conditions, such as seizures, may alter the cortical network and show a prolonged period of hyperactivity and an aberrant avalanche [20-22]. Simulations have indicated that the dynamic range of inputs is optimized in the critical state [6,7,17,23,24].…”
Section: Introductionmentioning
confidence: 99%